A new fiscal strategy for Ireland - Lane, Philip R. (Economic & Social Studies, 2009)
Around the world, fiscal policy has been accorded a prominent role in the debate on responding to the sharp economic slowdown. In large part, this reflects the limited effectiveness of monetary policy, once policy rates are close to zero and the persistent spread between inter-bank and policy rates renders ineffective the traditional monetary transmission mechanism through the bank lending channel. At a global level, the November 2008 and April 2009 summits of the G-20 group signalled the commitment of the world?s largest economies to fiscal expansion. At the December 2008 European Council meeting, the member countries of the European Union have also agreed a fiscal expansion plan, amounting to 1.5 per cent of EU GDP. However, at both the global and European levels, there is widespread agreement that the appropriate fiscal stance varies across countries, according to the individual circumstances of each economy.
Policy paper
Keywords: Fiscal policy; Economic governance; Ireland; Crisis